Calidad del servicio y lealtad del cliente en el Restaurante Mechita de la ciudad de Cajabamba. - Castillo Villalva, Margarita Feliciana (2015)
In Cajabamba city, department of Cajamarca, the agricultural and commercial activity is developed specially on Sundays. The foreign and natural people that come from the field and the city, dynamism the demand of services: food, generating high competence among the restaurants. The purpose of the research is support to support how the quality of service has influence in the level of loyalty of the customer in the restaurant of study. For this reason the problem of the research in: in what way the quality of service has influence in the loyalty of the customer in the Mechita restaurant in the city of Cajabamba? About the methodology, the method deductive – inductive, analytic- synthetic and systemic has been used; the main technique used was the survey that has been applied to a sample of 86 customers of a total population of 800 people by a week. Among the most important results we have: The quality of service present four fortresses (the seasoning, variety of dishes, quality of attention, quick service) and six weaknesses (physic building, external communication, personal presentation and low level of professionalism and a lack of attention of particular needs of the clients). About fidelity of clients, all the indicators are medium weaknesses and are in relation to the levels of buying, frequency of visits, recommendations to other people. In base of the results, and after the has been possible discussion in base experimental, transactional – correlational design., has demonstrated the hypothesis: “ The quality of service has influence in a positive way in the level of client fidelity in Mechita restaurant in Cajabamba city”; this is because there is a very close relation between the media of the variables ..The relation also has been explained theoretically with the studies of Barrosco, C ( 1999) cited by BARAHONA, P. (2009), y KOTLER, P. & ARMSTRONG, G. (2008); who think that the quality of service has influence in the fidelity of the client. Finally, some recommendations have been proposed, being the post important, improve the construction of the restaurant building, count with the list of prices, the staff should use the adequate cloth, proposed qualified personal and provide them capacitation and improve the administration using informatics technology in thee diverse processes.